2017
DOI: 10.15406/jbmoa.2017.05.00120
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubilizing Yeast Isolated and Characterized from Teff Rhizosphere Soil Collected from Gojam; Ethiopia

Abstract: Phosphorous is an essential macronutrient for plant growth and development. About 95-99% present in soil insoluble form. Phosphate solubilizing microorganisms can increase soil phosphate solubility and availability. This study was aimed to identify and evaluate phosphate solubilizing yeast from Teff rhizosphere soil. Yeasts were identified using Biolog Micro station identification system. Yeast isolates were screened and transferred to biolog universal yeast agar media. Pure yeast cells were suspended in steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(15 reference statements)
2
4
0
Order By: Relevance
“…The results indicated that only two yeast species, P. laurentii and W. anomalus , were able to solubilize the insoluble form of phosphate (Ca 3 (PO 4 ) 2 ), and zinc (ZnO and ZnCO 3 ). These results were similar to those of other previous studies which reported on the phosphate and zinc-solubilizing abilities of both yeast species [ 26 , 65 , 80 , 81 , 82 ]. Moreover, some species of yeast in the genera Aureobasidium, Barnettozyma, Candida, Holtermanniella, Lachancea, Pichia, Rhodotrula, Saccharomyces, Torulaspora have been recognized for their phosphate and zinc-solubilizing abilities [ 26 , 29 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results indicated that only two yeast species, P. laurentii and W. anomalus , were able to solubilize the insoluble form of phosphate (Ca 3 (PO 4 ) 2 ), and zinc (ZnO and ZnCO 3 ). These results were similar to those of other previous studies which reported on the phosphate and zinc-solubilizing abilities of both yeast species [ 26 , 65 , 80 , 81 , 82 ]. Moreover, some species of yeast in the genera Aureobasidium, Barnettozyma, Candida, Holtermanniella, Lachancea, Pichia, Rhodotrula, Saccharomyces, Torulaspora have been recognized for their phosphate and zinc-solubilizing abilities [ 26 , 29 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results were similar to those of other previous studies which reported on the phosphate and zinc-solubilizing abilities of both yeast species [ 26 , 65 , 80 , 81 , 82 ]. Moreover, some species of yeast in the genera Aureobasidium, Barnettozyma, Candida, Holtermanniella, Lachancea, Pichia, Rhodotrula, Saccharomyces, Torulaspora have been recognized for their phosphate and zinc-solubilizing abilities [ 26 , 29 , 80 , 81 , 82 , 83 , 84 ]. Additionally, a number of previous studies have reported that the insoluble mineral solubilization ability of yeast cultures can vary depending on the type of mineral and yeast species as well as the particular yeast strain [ 26 , 29 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several yeasts are known to produce mycocins (extracellular proteins) involved in inhibition of β -glucan synthesis in the cell wall of sensitive strains, which cause the death of the other species of yeast, moulds, and bacteria [ 16 ]. Yeast is involved in the process of dissolving soil-insoluble phosphates, transforming complex organic biomass into mineral compounds used by plants, and the synthesis of growth factors such as amino acids, vitamins, and enzymes [ 17 ]. There have been an increased number of studies concerning the isolation of endophytic yeasts that stimulate plant growth [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an indicator, bacteria strain as inoculants for different crop production is an appreciating starting research done by Ethiopian researcher. Hence, Gizaw B, et al [94] reported that Phichia norvegensis and Cryptococcus albidus var aerius were superior in phosphate solubilization and recommended as bio fertilizers for teff productivity. Additionally, Muleta D et al [95] also suggested that Pseudomonas spp.…”
Section: Current Trends and Future Prospects Of Phosphate Solublizing...mentioning
confidence: 99%